Study on insect diversity and pollination effect on the yield of elephant apple (Journal of Biodiversity Conservation and Bioresource Management, 2023)
An experiment was conducted from June to November 2021 at the Sher-e-Bangla Agricultural University in Dhaka to find out the insect diversity and pollination effects on the yield of elephant apple. Six flower visiting insects (Apis cerana, Apis dorsata, Xylocopa sp., Vespa sp., Camponotus copressus and Syrphes sp.) from five insect families (Apidae, Vespidae, Anthophoridae, Formicidae, and Syrphidae) under two orders (Hymenoptera and Diptera) were observed. Apidae (33.33%), Vespidae (16.67%), Formicidae (16.67%), Syrphidae (16.67%), and Anthoporidae (16.67%) visited flowers. Apis dorsata was the most frequent insect pollinator (47.62%), with 5.00 per flower on average. The Shannon-Wiener diversity index for species was 1.562. The highest foraging duration was recorded for Apis dorsata at 1.4 minutes per flower. Without netting and with netting, elephant apple plants produced 7.00 and zero (0.00) fruit per branch, respectively. Plants without netting had 464 kg of fruit per plant, 92.8 tonnes per ha of yield, and no fruit in the netting treatment.Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 75-82